THE INITIAL PHILOSOPHICAL WORLDVIEW OF TURKIC PEOPLES: BELIEF IN NATURE, MYTHOLOGICAL THINKING, AND PRE-ISLAMIC DEVELOPMENT STAGES - Norbutayev Islombek Musurmonovich (Web of Journals Publishing, 2025)
This scientific article is devoted to a systematic investigation of the genesis and evolution of the early philosophical worldview of Turkic peoples before the Islamic period. The study encompasses an analysis of fundamental elements such as nature worship, the structures of mythological thinking, and the paradigm of Tangrism, delving into their ontological, epistemological, and ethical foundations. The article seeks to delineate the historical trajectory of the development of these perspectives while assessing their transformative role within the spiritual and intellectual heritage of Turkic peoples. Furthermore, it elucidates the dialectical interrelationship between ancient belief systems and their philosophical reflection, thereby facilitating the reconstruction of the initial metaphysical concepts of Turkic societies. By integrating perspectives from the history of philosophy and cultural studies, this work contributes to a broader contextual understanding of the intellectual traditions of Turkic peoples, shedding light on their pre-Islamic philosophical underpinnings.
Keywords: Turkic peoples, philosophical worldview, nature worship, mythological thinking, pre-Islamic period, Tangrism, shamanism, connection with nature, world perception, ancient beliefs, philosophical development, mythology, traditions, spiritual heritage, historical stages.